Methods in the theory of hereditarily indecomposable Banach spaces - Argyros, S. (Spiros), 1950- (Memoirs of the American Mathematical Society, 2004)
Introduction General results about H.I. spaces Schreier families and repeated averages The space ${X= T [G, (\mathcal{S}_{n_j}, {\tfrac {1}{m_j})}_{j}, D]}$ and the auxiliary space ${T_{ad}}$ The basic inequality Special convex combinations in $X$ Rapidly increasing sequences Defining $D$ to obtain a H.I. space ${X_G}$ The predual ${(X_G)_*}$ of ${X_G}$ is also H.I. The structure of the space of operators ${\mathcal L}(X_G)$ Defining $G$ to obtain a nonseparable H.I. space ${X_G^*}$ Complemented embedding of ${\ell^p}, {1\le p <\infty}$, in the duals of H.I. spaces Compact families in $\mathbb{N}$ The space ${X_{G}=T[G, (\mathcal{S}_{\xi_j}, {\tfrac {1}{m_j})_{j}}, D]}$ for an ${\mathcal{S}_{\xi}}$ bounded set $G$ Quotients of H.I. spaces Bibliography.